Effects of folic acid on renal endothelial function in patients with diabetic nephropathy: results from a randomized trial - Schneider, Markus P.; Schneidert, Andreas; Jumar, Agnes; Kistner, Iris; Ott, Christian; Schmieder, Roland (Clinical Science, 2014)
Endothelial dysfunction has been shown to promote podocyte injury and albuminuria in diabetes, highlighting the importance of the interaction between renal endothelial cells and podocytes. Folic acid (FA) improves nitric oxide synthase (NOS) function and reduces progression of diabetic nephropathy in animal models. We tested whether high-dose FA treatment improves renal endothelial function and albuminuria in human subjects with incipient diabetic nephropathy. Following a double-blind, randomized, cross-over design, 28 patients with Type 2 diabetes and albuminuria were allocated to 4 weeks' treatment with placebo and high-dose FA (5 mg/day). Renal nitric oxide (NO) production determined as the response of renal plasma flow (RPF) to NOS inhibition with NG-monomethyl-L-arginine (L-NMMA) (4.25 mg/kg intravenously), renal oxidant stress as response of RPF to vitamin C infusion (3 mg/kg) and albuminuria were determined after each treatment phase. Neither the reduction in RPF to L-NMMA nor the increase in RPF to vitamin C infusion differed between treatment phases (?RPF to L-NMMA: -74±71 ml/min per m2 during placebo compared with -63±56 ml/min per m2 during FA, P=0.57; ?RPF to vitamin C: +93±118 ml/min per m2 compared with +94±108 ml/min per m2; P=0.70). In line with the lack of effect on the renal endothelium, albuminuria was not affected by FA treatment (110±179 mg/day during placebo compared with 87±146 mg/day during FA; P=0.12). High-dose FA treatment does not improve renal endothelial function and fails to reduce albuminuria in human subjects with diabetic nephropathy. Novel treatment options for oxidant stress and endothelial dysfunction in patients with diabetes are urgently needed.
EVALuna2:3679